THE INFLUENCE OF LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE OF PT GEORG FISCHER INDONESIA THROUGH MOTIVATION AS INTERVENING VARIABLE - Mutiaram, Rahnian; Ali Iqbal, Muhammad (Dinasti International Journal of Management Science, 2021)
This study aims to examine the influence of leadership and organizational culture on employee performance through motivation as a mediation. The number of respondents in this study were 116 respondents. Where all of them are employees of PT Georg Fischer Indonesia. This research is a quantitative research. Research data obtained from the results of filling out the questionnaire. The research data were then analyzed using the Partial Least Square analysis technique with the help of the SmartPLS program. The results of the analysis using the PLS analysis technique provide the following conclusions: Leadership and organizational culture has a positive and significant effect on motivation, leadership and organizational culture has a positive and siginificant effect on employee performance, motivation had a positive and siginificant effect on employee performance, and motivation could mediate the indirect effect of leadership and organizational culture on employee performance.